Comprensión lectora y textos literarios: una propuesta psicopedagógica - Méndez Anchía, Silvia (2012)
The essay presents an insight on the reading of literary texts in the Third Level General Basic Education in relation with the text students’ understanding of the text and their academic achievement in general. First, a short presentation of the guidelines for reading comprehension of the Spanish study programs from the Ministry of Education is given. Next, two concepts are discussed: the psychopedagogical concept that works as the baseline, and the order of the different levels of reading. Then, a series of considerations about the six levels of reading comprehension proposed by the Ministry of Education are developed (literal, reorganization of the explicit, inferential, evaluative, appreciative, applicative, and recreational). The considerations are based on the demands for knowledge implied in the reading of literature texts. Finally, the role of reading in the adolescents’ academic achievement and behavior modification is discussed.